2007
DOI: 10.1593/neo.06823
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic K-Ras Signals through Epidermal Growth Factor Receptor and Wild-Type H-Ras to Promote Radiation Survival in Pancreatic and Colorectal Carcinoma Cells

Abstract: Pancreatic and colorectal carcinomas frequently express oncogenic/mutant K-Ras that contributes to both tumorigenesis and clinically observed resistance to radiation treatment. We have previously shown that farnesyltransferase inhibitors (FTI) radiosensitize many pancreatic and colorectal cancer cell lines that express oncogenic K-ras at doses that inhibit the prenylation and activation of H-Ras but not K-Ras. In the present study, we have examined the mechanism of FTI-mediated radiosensitization in cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 22 publications
5
46
0
Order By: Relevance
“…Yet, as the amount of basal p-AKT reduction does not follow the efficient downregulation of K-Ras protein by siRNA, a function of H-Ras and/or N-Ras in stimulating AKT phosphorylation directly through interaction with PI3K, as it was proposed earlier (33,34,45), cannot be ruled out at present. Furthermore, recently, in line with our data, it was shown that K-RAS mutation in human pancreatic and colorectal cancer cells activates EGFR and H-Ras via an autocrine production of EGFR ligands, which in turn enhances postirradiation survival (64). From the data published by Cengel et al (64) and our data presented herein, it can be postulated that a compensatory effect may exist, which, via EGFR-dependent H-Ras activity, can enhance basal level of p-AKT independent of a direct interaction with K-Ras protein.…”
Section: Mol Cancer Res 2007;5(8) August 2007supporting
confidence: 87%
See 1 more Smart Citation
“…Yet, as the amount of basal p-AKT reduction does not follow the efficient downregulation of K-Ras protein by siRNA, a function of H-Ras and/or N-Ras in stimulating AKT phosphorylation directly through interaction with PI3K, as it was proposed earlier (33,34,45), cannot be ruled out at present. Furthermore, recently, in line with our data, it was shown that K-RAS mutation in human pancreatic and colorectal cancer cells activates EGFR and H-Ras via an autocrine production of EGFR ligands, which in turn enhances postirradiation survival (64). From the data published by Cengel et al (64) and our data presented herein, it can be postulated that a compensatory effect may exist, which, via EGFR-dependent H-Ras activity, can enhance basal level of p-AKT independent of a direct interaction with K-Ras protein.…”
Section: Mol Cancer Res 2007;5(8) August 2007supporting
confidence: 87%
“…Furthermore, recently, in line with our data, it was shown that K-RAS mutation in human pancreatic and colorectal cancer cells activates EGFR and H-Ras via an autocrine production of EGFR ligands, which in turn enhances postirradiation survival (64). From the data published by Cengel et al (64) and our data presented herein, it can be postulated that a compensatory effect may exist, which, via EGFR-dependent H-Ras activity, can enhance basal level of p-AKT independent of a direct interaction with K-Ras protein.…”
Section: Mol Cancer Res 2007;5(8) August 2007supporting
confidence: 87%
“…The possible mechanisms by which this pathway regulates NPC proliferation include mutations in PI3K, PTEN deleted from chromosome 10 (PTEN), and Ras oncogene, as well as EGFR amplification (6)(7)(8). Previous studies showed that PI3K/Akt/mTOR signaling is frequently activated in many cancers, including lung, gastric, renal, and ovarian cancers (9)(10)(11)(12), and inhibition of this pathway could increase radiosensitivity (8,(13)(14)(15)(16)(17)(18). NPC cell lines and tissues also overexpressed phosphorylated Akt (p-Akt; refs.…”
Section: Introductionmentioning
confidence: 99%
“…Many abnormal gene expressions and dysregulated signaling pathways play important roles in tumorigenesis and tumor progression of crc (1)(2)(3)(4). egFr is a transmembrane tyrosine kinase receptor that, on ligand binding, triggers two main signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…egFr is a transmembrane tyrosine kinase receptor that, on ligand binding, triggers two main signaling pathways. these include the rAs-rAF-MApK axis, which is mainly involved in cell proliferation, and the pI3K-pten-AKt pathway, which is mainly involved in cell survival and motility (2,5). Mutation in KrAs, BrAF or pIK3cA results in continuous activation of the downstream rAs-MApK or pI3K pathways, regardless of whether the egFr is activated (6,7).…”
Section: Introductionmentioning
confidence: 99%